Managing reputation in a transparent world - Satterthwaite, Christopher (Henry Stewart Talks, 2010)
Reputation management has become as important as brand management, Fragmented and connected media enable the 'social evaluation' that reputation is, to be disseminated and amplified over the internet and all digital media, Your reputation is a risk as well as an opportunity, Brand reputation has replaced brand image